Surface crystal-orientation-dependent second-order nonlinear optical properties of cubic boron arsenide (c-BAs) - Lipeng Zhu; Yachao Ma; Chuyi Zhou; Tanwen Lai; Aochi Jia; Yipeng Zheng; Kaili Ren; Dongdong Han; Jun Dong; Ze Xue; Yani Ren; Qiyi Zhao; et al. (Results in Physics)
Cubic boron arsenide (c-BAs) has a potential in the integrated optoelectronic fields because of the outstanding thermal conductivity and carrier mobility. However, there is relatively little research on the nonlinear optical properties of c-BAs. Herein, the electronic, linear, and nonlinear second-order optical properties have been systematically investigated by the first principles calculation method. The energy band structure demonstrates that c-BAs is an indirect bandgap semiconductor. The isotropic complex dielectric functions and the derived linear optical parameters have been obtained, such as complex refractive index and reflectivity. The dispersion of the second-order nonlinear optical coefficient also been acquired. The dependence of the surface anisotropic second harmonic generation (SHG) patterns on the azimuth angle, polarization angle, and incidence angle for c-BAs (001), (110), and (111) facet have been calculated and discussed. The optical properties prove that c-BAs has the ability in integrated optoelectronic devices.